Molecular Characterization of Some Syrian Pomegranate (Punica granatum L.) Genotypes - Al-Mousa, Rehab; Al-Biski, Fahed; Alshaal, Alaa (Jordan Journal of Agricultural Sciences, 2019)
Considering the high level of morphological diversity in Syrian pomegranate (Punica granatum L.) genotypes, this study was conducted to evaluate the genetic variation among five pomegranate genotypes using twenty inter simple sequence repeat (ISSR) markers. Twelve ISSR primers were successfully used as fingerprinting tools and amplified 137 DNA fragments out of which 78 were polymorphic (56.93%). Primers (17, NLSSR3, 16) showed the highest polymorphism percentage (90.41, 80.00, 76.47%, respectively) with the highest number of unique bands (6, 6, 9 respectively). Genotype C amplified the highest number of DNA fragments (115) and unique bands (13). Polymorphism information content (PIC) ranged from 0.449 to 0.768, while genetic diversity (GD) ranged from 0.56 to 0.80. The genetic distance ranged from 0.26 to 0.37. Some genotypes showed wide divergence (C and A; C and D), while genotypes A and B were closely related. The unweighted pair‐grouped method with arithmetic average (UPGMA)dendrogram grouped the genotypes into two clusters. These results indicated that the ISSR technique was sufficiently informative and powerful to assess genetic variability in pomegranate.